Cauda equina syndrome after induction of spinal anesthesia - (:unkn) unknown (My University, 2004)
In this report the authors present a case of cauda equina syndrome that developed following induction of spinal anesthesia in a patient who had no apparent preexisting bleeding abnormality. An acute subdural hematoma caused the syndrome and was believed to have resulted from direct vascular trauma during administration of spinal anesthesia or from vascular trauma combined with thrombocytopenia in the postoperative period.